Pedagogical scaffolding strategies for supporting students with mathematical learning difficulties in special education - Anggreni, Melda; Anwar; Munzir, Said (Jurnal Elemen, 2025)
Students with special needs, including those with speech impairments, often face challenges in learning mathematics and therefore require specialised strategies, such as scaffolding, to enhance their mathematical understanding. This study aimed to examine how scaffolding strategies support students with speech impairments in overcoming difficulties in learning mathematics in a special school setting. This qualitative case study involved one teacher and five students with speech impairments, selected through purposive sampling. Data were collected through observations, tests, interviews, and audio and video recordings. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing and verification. The findings show that the teacher’s scaffolding aligned with six aspects of the Mäkinen and Mäkinen framework: activation, presence, sensitivity, assistance, trust, and autonomy. Activation and assistance were the most strongly associated with improved conceptual understanding. The students demonstrated the ability to define, represent, and calculate the perimeter of squares and rectangles. Visual aids, concrete objects, and multimodal communication (oral, gestural, and sign language) enhanced understanding. Integrating visual, kinesthetic, and nonverbal strategies provides meaningful support for students with speech impairments, and the six-dimensional scaffolding framework serves as a practical guide for inclusive instructional design.